2009
DOI: 10.1016/j.ijcard.2007.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and connective tissue features in 5 Italian patients with homocystinuria

Abstract: Homocystinuria is a metabolic disorder associated with defects in genes encoding for methionine metabolism enzymes. Vascular and connective tissue manifestations such as deep venous thrombosis, ectopia lentis and skeletal alterations are the major clinical features.We investigated the clinical manifestations of 5 Italian homocystinuric patients, performed mutation screening analysis on cystationine beta-synthase (CBS) gene and searched for genotype/phenotype correlations.We detected mild cardiovascular and ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In addition, renal arterial pathology causing decreased elimination of homocysteine creates a self-perpetuation of cardiovascular risk [9]. Researchers have also reported fibrillin-1 protein modification causing alterations in connective tissues resulting in structural damages such as cardiac valvulopathies along with ocular and skeletal malformations, as seen in Marfan's syndrome [10]. This might have been the basis of the DCM seen in our case.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, renal arterial pathology causing decreased elimination of homocysteine creates a self-perpetuation of cardiovascular risk [9]. Researchers have also reported fibrillin-1 protein modification causing alterations in connective tissues resulting in structural damages such as cardiac valvulopathies along with ocular and skeletal malformations, as seen in Marfan's syndrome [10]. This might have been the basis of the DCM seen in our case.…”
Section: Discussionsupporting
confidence: 54%
“…This prompted us to investigate in the present study a reportedly mild pathogenic mutation associated with classical homocystinuria, a proline-to-leucine substitution at residue 49 in human CBS [ 44 46 ]. The recombinant CBS p.P49L variant was expressed in E. coli , purified, and characterized both structurally and functionally.…”
Section: Discussionmentioning
confidence: 99%
“…The 146 C>T transition in exon 1 of the CBS gene generates the clinically relevant p.P49L variant, identified in patients with classical homocystinuria [ 44 46 ]. The mutation results in mild to moderate symptoms and sporadic responsiveness to vitamin B6 treatment.…”
Section: Introductionmentioning
confidence: 99%
“…7 The skeletal manifestations of this disorder include osteoporosis and limitation of joint mobility, and its skin manifestations include thin, transparent skin and striae, which are the consequences of collagen underproduction. [8][9][10] Histomorphometric and histologic analyses revealed that CBS-deficient mice have wrinkled skin with thinning of the dermis. 10 Shuster 11 suggests that the changes in skin collagen correspond to changes in bone density.…”
mentioning
confidence: 99%